Pengembangan Karir dan Profesionalisme Guru Melalui Karya Ilmiah - Syamsir, Syamsir; Putra, Ideal; Lanin, Dasman (JESS (Journal of Education on Social Science); Vol 3 No 1 (2019): Relationship between Government and CommunityDO - 10.24036/jess/vol3-iss1/167, 2019)
This article (study) was summarized as a reflection of writer s experience s in conducting Community Service program among teachers of SMAN 1 and SMAN 4 in Solok Selatan Regency. This study was inspired by various conditions that indicate d the decline in professionalism of teachers in various schools in Solok Selatan Regency . This issue wa s , among others , reflected in the low quality and competence of teachers in creating scientific work. As one of the educational actors in schools, every teacher should have the ability to develop their career and professionalism through the creation of scientific work. Therefore the roles and responsibilities of teachers are highly required to be able to create scientific work.The teacher's ability to create scientific work will greatly determine the success of the teacher in their career and at the same time it would determine the quality of education as a whole. Based on this condition, various career development policies and programs and teacher professionalism we re needed, among others , in the form of increasing capacity in creating scientific works for high school teachers in Solok Selatan Regency. These career development activities and programs and teacher professionalism need ed to be conducted collaboratively and synergistically between the local government, schools, universities, and the Education Quality Assurance Agency (LPMP ).